2020
DOI: 10.21203/rs.2.15999/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medication omission rates in New Zealand Residential Aged Care Homes: a national description

Abstract: Background A medication omission is an event where a prescribed medication is not taken before the next scheduled dose. Medication omissions are typically classed as errors within Residential Aged Care (RAC) homes, as they have the potential to lead to harm if poorly managed, but may also stem from good clinical decision-making. This study aimed to quantify the incidence, prevalence, and types of medication omissions in RAC homes on a national scale, using a New Zealand-based sample. Methods We conducted retro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…An Australian study reported a significant improvement of approximately 29% in the probability of medication errors reduction due to effective and improved communication between the health care workers in the hospital [21] . Furthermore, a study of New Zealand demonstrated that nurses' with advanced education led to a decrease in missed dose error by 26.7% [22] and one more interventional study investigated the impact of nurse education on the incidence of omitted medication doses among hospitalized patients and found a significant reduction of missed doses error after intervention [23] . Electronic prescribing can also be an efficient way to decrease missed dose errors [24] .…”
Section: *Statistical Significantmentioning
confidence: 99%
“…An Australian study reported a significant improvement of approximately 29% in the probability of medication errors reduction due to effective and improved communication between the health care workers in the hospital [21] . Furthermore, a study of New Zealand demonstrated that nurses' with advanced education led to a decrease in missed dose error by 26.7% [22] and one more interventional study investigated the impact of nurse education on the incidence of omitted medication doses among hospitalized patients and found a significant reduction of missed doses error after intervention [23] . Electronic prescribing can also be an efficient way to decrease missed dose errors [24] .…”
Section: *Statistical Significantmentioning
confidence: 99%